"We All Have Stories": Black Muslim Immigrants' Experience With the Police. (July 2020) - Ellis, B. Heidi; Lincoln, Alisa K.; Abdi, Saida M.; Nimmons, Elizabeth A.; Issa, Osob; Decker, Scott H.
Understanding the relationships between immigrants and refugees and the police is a critical research task with implications for both community–police partnerships and the effectiveness of law enforcement efforts. This study contributes to such an understanding by examining perceptions of police and police interactions among Somali immigrants and refugees (both first and second generation) in three communities in the United States and Canada. This article presents in-depth analyses of qualitative interview data and draws upon multiple theoretical perspectives, specifically procedural justice and minority group threat theory. These perspectives have been employed to account for police–minority relationships in other works and we extend their application to a new group. We find that despite some evidence of positive interactions with police, current policing could do more to establish community trust and implement principles of procedural justice with Somalis in the United States and Canada. This article also finds support for the minority group threat theory in that study participants perceive that they experience harsher and more frequent policing due to their multiple marginalized statuses (Black, immigrant, and Muslim). Implications for both Somali immigrants/refugees and law enforcement are discussed.